1998
DOI: 10.2307/3433967
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Screening of Chemical Releases and Environmental Equity Analysis of Populations Proximate to Toxic Release Inventory Facilities in Oregon

Abstract: This review shows the equal or greater importance of leaded gasoline-contaminated dust compared to lead-based paint to the child lead problem, and that soil lead, resulting from leaded gasoline and pulverized lead-based paint, is at least or more important than lead-based paint (intact and not pulverized) as a pathway of human lead exposure. Because lead-based paint is a high-dose source, the biologically relevant dosage is similar to lead in soil. Both lead-based paint and soil lead are associated with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 24 publications
1
47
1
1
Order By: Relevance
“…Since block group traffic density is related to vehicle emissions and was moderately correlated with the ambient concentrations of several vehicle-related pollutants, children living in these areas have higher potential for exposure. Other studies in the US have found that low-income neighborhoods and communities of color are more likely to be located near sources of pollution (Perlin et al, 1995;Korc, 1996;Neumann et al, 1998;Perlin et al, 1999Perlin et al, , 2001Morello-Frosch et al, 2002). Our results, from a large and heterogeneous state, provide further evidence that low-income and people of color are more likely to live near sources of toxic emissions, in this case freeways and major roads.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Since block group traffic density is related to vehicle emissions and was moderately correlated with the ambient concentrations of several vehicle-related pollutants, children living in these areas have higher potential for exposure. Other studies in the US have found that low-income neighborhoods and communities of color are more likely to be located near sources of pollution (Perlin et al, 1995;Korc, 1996;Neumann et al, 1998;Perlin et al, 1999Perlin et al, , 2001Morello-Frosch et al, 2002). Our results, from a large and heterogeneous state, provide further evidence that low-income and people of color are more likely to live near sources of toxic emissions, in this case freeways and major roads.…”
Section: Discussionsupporting
confidence: 70%
“…A census tract level analysis in three parts of the US observed that African Americans and those living below the poverty level were more likely to live closer to the nearest industrial facility and to live near multiple facilities (Perlin et al, 1999(Perlin et al, , 2001. A similar evaluation conducted in Oregon found that industrial facilities were disproportionately located in minority and low-income neighborhoods, but there was no relation between hazard ranking and overall socioeconomic status (SES) of the community (Neumann et al, 1998). An assessment of ozone exposure in Southern California concluded that low-income areas generally experience higher ozone concentrations than high-income areas (Korc, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1b). These two distances were chosen to correspond to those used in environmental justice studies conducted in the USA (Neumann et al, 1998;Abel 2008;Kearney and Kiros, 2009) and to approximate the dimensions of Toronto census tracts (average area = 1.2 km 2 ).…”
Section: Spatial Assessment Of Air Pollutionmentioning
confidence: 99%
“…The effects were stronger when weights were applied to account for toxicity of the waste. However, in another study the relationship between the hazard ranking of a toxic release inventory facility and a neighbourhood's socio-economic status was not significant (Neumann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One rare study attempting to tease out the causal direction between the placement of toxic sites and the presence of racial/ethnic minorities focused on tracts within the city of Los Angeles over three decades (Pastor et al 2001). This limited literature suggests an important need for further longitudinal studies.Our study addresses the following questions: 1) what is the relative proximity to toxic waste sites for minority groups over a ten year period from 1990 to 2000; 2) do neighborhoods with more highly educated residents experience less proximity to toxic waste sites; and 3) do these effects differ if we take into account the toxicity of the emitted wastes (Ash, and Fetter 2004;Brooks, and Sethi 1997;Neumann, Forman, and Rothlein 1998;Sicotte, and Swanson 2007). Beyond our longitudinal approach, we assess the impact of toxic sites on neighborhood Disproportionate toxicity proximity 6 residents by measuring the pounds of release weighted by a measure of its toxicity, and apportioning this value to a one-mile circle around the site rather than simply attributing it to the census tract in which the site is located (other studies using this approach include Bolin et al 2002;Mohai, and Saha 2006).…”
mentioning
confidence: 99%